STRATEGI PROMOSI WISATA RELIGI MAKAM SYEKH SURGI MUFTI - Devi Noviyanti (Alhadharah: Jurnal Ilmu Dakwah, 2018)
Indonesia is a pluralistic country. This plurality produces Indonesia rich in various aspects, such as ethnicity, language, culture and religion so that it supports the fields for sustainable development. South Kalimantan, which is one of the provinces in Indonesia, has a great potential to be developed into an attractive business opportunity because of the number of tourist objects that can be visited by tourists, both domestic and foreign. South Kalimantan offers typical local cultural characters such as the typical Banjar traditional house, Agung Amuntai Temple, Floating Market, typical Banjar fabric craftsmen village, Sasirangan and others. In addition to offering natural and cultural attractions. South Kalimantan is also famous for its religious tourism where one is expected to be the tomb of the famous Ulama which is visited by pilgrims, namely the dome of Surgi Mufti KH. Jamaluddin who also came from a great ulama from South Kalimantan, Sheikh Muhammad Arsyad Al-Banjari. The Surgi Mufti Dome is also one of the pilgrimage attractions designated as cultural heritage sites approved by the Republic of Indonesia Law Number 11 of 2010. The Dome of the Surgi Mufti is located on Jalan Mesjid Jami, Surgi Mufti Village, North Banjarmasin District, Banjarmasin City. In order to develop tourism objects in the South Kalimantan region, one of them is the Tomb of Sheikh Surgi Mufti, so tourism promotion or communication efforts are needed as a strategy that can provide information on tourist destinations in detail and clearly